Studi Eksperimen Efek Aliran Udara dan Waktu Pembakaran Konsumsi terhadap Efisiensi Pembakaran pada Kompor Bio Massa - Suheri Suheri; Hamdani Umar; Darlis Turnip (Universitas Muhammadiyah Tangerang, 2026)
Economic growth and population in Indonesia have experienced a very rapid increase, resulting in a surge in energy and fuel consumption. The increase in energy and fuel consumption, especially those sourced from fossil fuels for community needs that are not well managed, will have a negative effect, so that the utilization of biomass energy is the main focus in the transition process and efforts to achieve energy independence. The study was conducted on a type of biomass-based fuel in the form of biopellets consisting of a mixture of sawdust and rice bran, which was burned in a biomass stove measuring 520 x 250 x 190 mm. Variations in controlled air flow were 3 m/s, 6 m/s, and 9 m/s using a blower, as well as variations in combustion duration that were increased for 60 seconds, 120 seconds, 180 seconds, 240 seconds, 300 seconds, 360 seconds, 420 seconds, 480 seconds, 540 seconds, and 600 seconds, characterization was carried out to determine combustion efficiency and thermal efficiency with an experimental approach. Tests showed that an air velocity of 9 m/s produced the highest thermal efficiency of 46.349% for biopellets and 41.381% for wood at a combustion duration of 600 seconds. The findings of this study are expected to serve as a reference in designing efficient and effective biomass stoves, and can be practically implemented in the field. Furthermore, an air velocity of 9 m/s and a combustion time of 600 seconds are crucial parameters recommended as optimal settings for its operation.